Arabidopsis thaliana Myosin XI is Necessary for Cell Fate Determination in Root Epidermis - Kevin Kuo (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
Root hairs are specialized epidermal cells with important functions, such as absorbing water and nutrients from soil. In Arabidopsis thaliana, root hairs develop in a strict position-dependent mechanism that results in alternating longitudinal hair and non-hair cell files along the surface of the root. This invariant pattern is determined, in large part, by a complex network of transcription factors in the epidermis. However, epidermal cells are also highly plastic and have the ability to promote root hair growth even after the hairless cell fate has been determined by transcriptional control. Recently, it has been observed that the mutants of a specific isoform of class XI myosins, mya1, grow ectopic root hairs in Arabidopsis. Since class XI myosin proteins are actin-based molecular motors that transport intracellular organelles or protein complexes, it is possible that MYA1 also has a role in the trafficking of those transcription factors and their upstream regulators that are involved in cell-type patterning. Here, three promoter-GUS (beta-glucuronidase) constructs were utilized to determine what possible cargo or cargoes MYA1 may carry in this signal-transduction pathway. GL2::GUS expression in the roots of 4- to 6-day-old seedlings was first analyzed to determine any differences in patterning between wild-type and mutant genetic backgrounds. The results suggested that the elimination of MYA1 did not affect the expression patterning of GL2, which is the output of the signaling pathway. MYA1, thus, may not be involved in the transcriptional regulation that determines epidermal cell fate in Arabidopsis. It also suggested that MYA1 may then act on the hormonal or nutrient starvation response in root hair development to override the default cell fates set by the network of transcription factors.